Stl1 transporter mediating the uptake of glycerol is not a weak point of Saccharomyces kudriavzevii's low osmotolerance - Zemančíková, J; Papoušková, K; Peréz-Torrado, R; Querol, A; Sychrová, H (Letters in applied microbiology, 2019)
Saccharomyces kudriavzevii is a nonconventional and rather osmosensitive yeast with a high potential of use in fermentation processes. To elucidate the basis of its relative osmosensitivity, the role of the STL1 gene encoding a putative glycerol uptake system was studied. Under higher osmotic pressure, the addition of a low amount of glycerol to the growth medium improved the growth of S. kudriavzevii and the expression of the STL1 gene was highly induced. Deletion of this gene decreased the strain's ability to grow in the presence of higher concentrations of salts and other solutes. Moreover, the mutant had a disturbed homeostasis of intracellular pH. Expression of the SkSTL1 gene in Saccharomyces cerevisiae complemented the osmosensitivity of the S. cerevisiae hog1Δ stl1Δ mutant, and the gene's tagging with GFP localized its product to the plasma membrane. Altogether, a deficiency in glycerol uptake did not seem to be the reason for S. kudriavzevii's low osmotolerance; its Stl1 transporter properly contributes to the regulation of intracellular pH and is crucial to its survival of osmotic stress. SIGNIFICANCE AND IMPACT OF THE STUDY: An increasing demand for food products with benefits for human health turns the attention to less-exploited nonconventional yeasts with interesting traits not found in Saccharomyces cerevisiae. Among them, Saccharomyces kudriavzevii has good potential for aroma-compound production, fermentations and other biotechnological applications, but it is less adapted to stressful industrial conditions. This report studied S. kudriavzevii relative osmosensitivity and its capacity for active glycerol uptake. The results obtained (on the activity and physiological function of S. kudriavzevii glycerol transporter) may contribute to a further engineering of this species aiming to improve its osmotolerance.
Keywords: biologický transport; Osmotic Pressure; buněčná membrána; fermentace; Glycerol; fyziologický stres; delece genu; Saccharomyces cerevisiae; osmotický tlak; Cell Membrane; Biological Transport; Gene Deletion; mitogenem aktivované proteinkinasy; membránové transportní proteiny; Fermentation; Membrane Transport Proteins; Saccharomyces cerevisiae - proteiny; Mitogen-Activated Protein Kinases; glycerol; Stress, Physiological; Saccharomyces cerevisiae Proteins